The State of the Science in Universal Design: Emerging Research and Developments - L. Maisel, Jordana (Bentham Science Publishers, 2012)
The Rehabilitation Engineering Research Center on Universal Design and the Built Environment (RERC-UD), a federally funded research center located in The University at Buffalo, hosted a series of State of the Science (SOS) Activities in 2008. The SOS activities generated a large number of papers on both research and the practice of universal design in community infrastructures, public buildings, and housing. This Ebook contains a selected group of these papers that provide a survey of notable developments in the field, reflections on how research and practice can be advanced further, and propose an agenda for the near future. It is hoped that the book will be found useful for researchers, students and practitioners in this field.